(untitled) (Heritage, 2025)
Family entrepreneurship is a pillar of local economies in the Western Balkans, but the women involved often remain invisible in formal ownership, decision-making and management structures. The introduction of artificial intelligence into business processes further complicates existing gender inequalities. On the one hand, artificial intelligence offers new opportunities for digital transformation and more flexible work models within family entrepreneurship, and on the other, it reproduces existing forms of discrimination through algorithmic biases and unequal access to technologies. This paper analyzes how modern lifestyles affect the position of women in family entrepreneurship in the light of digital transformation and innovations based on artificial intelligence. The paper raises the question of how women’s contributions in digitally transformed family businesses can be legally recognized and protected. The conclusion points to the need for more inclusive digital policies, which do not view artificial intelligence exclusively as a technical, but also as a socially and legally relevant phenomenon.